Hubungan antara Stres dengan Motivasi Belajar pada Mahasiswa Tingkat Pertama Fakultas Kedokteran dan Ilmu Kesehatan Universitas Warmadewa - Dita Martina Mahardhika; Sri Ratna Dewi; I Wayan Eka Arsana (Fakultas Ilmu Kedokteran dan Ilmu Kesehatan, Universitas Warmadewa, 2023)
Stress is a mental health problem that can occur in medical students. Stress causes ineffective learning. Ineffective studies can lead to lower motivation and possible failure in education. The purpose of this study was to determine the relationship between stress and learning motivation in first-year students of the Faculty of Medicine and Health Sciences, Warmadewa University. This study uses an analytical method with a cross-sectional approach. The total sampling was based on the inclusion and exclusion criteria. Collecting data on stress levels and learning motivation using a questionnaire. Data analysis using univariate and bivariate analysis Spearman Rank Correlation test. The final result of the univariate analysis, most of the respondents experienced very severe stress levels (65.4%) and had low learning motivation (73.1%). Based on the bivariate analysis with the Spearman Rank Correlation test, it was found that there was a significant relationship between stress and learning motivation with p = 0.000 (p <0.05) and the correlation coefficient value is -0.423. Students are expected to be able to participate in stress prevention in the high school area and further researchers are expected to add other factors that influence the relationship between stress and learning motivation.